2015
DOI: 10.1186/s12917-015-0488-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune efficacy of five novel recombinant Bordetella bronchiseptica proteins

Abstract: BackgroundThe Gram-negative pathogen Bordetella bronchiseptica causes acute and chronic respiratory infection in a variety of animals. Currently, there is no vaccine to prevent these infections. To identify useful candidate antigens for such a vaccine, five B. bronchiseptica genes including amino acid ATP-binding cassette transporter substrate-binding protein (ABC), lipoprotein (PL), outer membrane porin protein (PPP), leu/ile/val-binding protein (BPP), and conserved hypothetical protein (CHP) were cloned and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 30 publications
(30 reference statements)
0
11
0
Order By: Relevance
“…Previously, challenge protection studies in mice revealed five types of immune proteins from B. bronchiseptica that served as candidate antigens for the rabbit subunit vaccine, and the highest protection rate was observed for the outer membrane porin (Liu et al . ). In the present study, the OMPP of B. bronchiseptica was successfully expressed in E. coli .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, challenge protection studies in mice revealed five types of immune proteins from B. bronchiseptica that served as candidate antigens for the rabbit subunit vaccine, and the highest protection rate was observed for the outer membrane porin (Liu et al . ). In the present study, the OMPP of B. bronchiseptica was successfully expressed in E. coli .…”
Section: Discussionmentioning
confidence: 97%
“…The protective effects of the outer membrane porin protein (OMPP) and putative lipoprotein were better than the other proteins, and the protection rates were 62·5 and 50% respectively (Liu et al . ). Therefore, the purpose of this study was to determine whether OMPP represents a potentially useful vaccine immunogen for rabbits against B. bronchiseptica .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…This confirmed the antigenicity of seven of the nine proteins. Bordetella bronchiseptica (B. bronchiseptica) causes acute and chronic respiratory infection in a variety of animals [167]. Currently, there is no vaccine to prevent these infections.…”
Section: Prediction Of Immunogens For Veterinary Medicinementioning
confidence: 99%
“…Currently, there is no vaccine to prevent these infections. Liu et al [167] analyzed five B. bronchiseptica antigens, as defined by VaxiJen, including amino acid ATP-binding cassette transporter substrate-binding protein (ABC), lipoprotein (PL), outer membrane porin protein (PPP), leu/ile/ val-binding protein (BPP), and conserved hypothetical protein (CHP). The murine immune responses to individual recombinant proteins were measured, with each tested protein inducing high antibody titers.…”
Section: Prediction Of Immunogens For Veterinary Medicinementioning
confidence: 99%